Development and therapeutic evaluation of 5D3(CC-MLN8237)3.2 antibody-theranostic conjugates for PSMA-positive prostate cancer therapy - Liatsou, Ioanna; Assefa, Betelhem; Liyanage, Wathsala; Surasinghe, Sharmane; Nováková, Zora; Bařinka, Cyril; Gabrielson, Kathleen; Raman, Venu; Artemov, Dmitri; Hapuarachchige, Sudath (Frontiers in Pharmacology, 2024)
Prostate cancer (PC) is an aggressive cancer that can progress rapidly and eventually become castrateresistant prostate cancer (CRPC). Stage IV metastatic castrate-resistant prostate cancer (mCRPC) is an incurable late-stage cancer type with a low 5-year overall survival rate. Targeted therapeutics such as antibody-drug conjugates (ADCs) based on high-affinity monoclonal antibodies and potent drugs conjugated via smart linkers are being developed for PC management. Conjugating further with in vitro or in vivo imaging agents, ADCs can be used as antibody-theranostic conjugates (ATCs) for diagnostic and image-guided drug delivery. In this study, we have developed a novel ATC for PSMA(+) PC therapy utilizing (a) anti-PSMA 5D3 mAb, (b) Aurora A kinase inhibitor, MLN8237, and (c) for the first time using tetrazine (Tz) and trans-cyclooctene (TCO) click chemistry-based conjugation linker (CC linker) in ADC development. The resulting 5D3(CC-MLN8237)3.2 was labeled with suitable fluorophores for in vitro and in vivo imaging. The products were characterized by SDS-PAGE, MALDI-TOF, and DLS and evaluated in vitro by optical imaging, flow cytometry, and WST-8 assay for cytotoxicity in PSMA(+/-) cells. Therapeutic efficacy was determined in human PC xenograft mouse models following a designed treatment schedule. After the treatment study animals were euthanized, and toxicological studies, complete blood count (CBC), blood clinical chemistry analysis, and H&E staining of vital organs were conducted to determine side effects and systemic toxicities. The IC50 values of 5D3(CC-MLN8237)3.2-AF488 in PSMA(+) PC3-PIP and PMSA(-) PC3-Flu cells are 8.17 nM and 161.9 nM, respectively. Pure MLN8237 shows 736.9 nM and 873.4 nM IC50 values for PC3-PIP and PC3-Flu cells, respectively. In vivo study in human xenograft mouse models confirmed high therapeutic efficacy of 5D3(CC-MLN8237)3.2-CF750 with significant control of PSMA(+) tumor growth with minimal systemic toxicity in the treated group compared to PSMA(-) treated and untreated groups. Approximately 70% of PSMA(+) PC3-PIP tumors did not exceed the threshold of the tumor size in the surrogate Kaplan-Meyer analysis. The novel ATC successfully controlled the growth of PSMA(+) tumors in preclinical settings with minimal systemic toxicities. The therapeutic efficacy and favorable safety profile of novel 5D3(CC-MLN8237)3.2 ATC demonstrates their potential use as a theranostic against aggressive PC.